2007
DOI: 10.1242/jcs.012468
|View full text |Cite
|
Sign up to set email alerts
|

In vivo movement of the type V myosin Myo52 requires dimerisation but is independent of the neck domain

Abstract: SummaryIn vivo movement of the type V myosin Myo52 requires dimerisation but is independent of the neck domain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
5
19
2
Order By: Relevance
“…This simple approach supports the ultimate controlled experiment: the simultaneous imaging of two genetically distinct cells in the same field of view, where one culture is labeled with a fluorescent lectin whereas the other is not ( Fig. 1B; Beinhauer et al 1997;Alvarez-Tabarés et al 2007;Grallert et al 2007;Attanapola 2009;Martín-García and Mulvihill 2009). Alternatively, an additional fusion protein at a distinct location that emits at a different wavelength can be incorporated into the control strain (Fig.…”
Section: Mountingsupporting
confidence: 59%
“…This simple approach supports the ultimate controlled experiment: the simultaneous imaging of two genetically distinct cells in the same field of view, where one culture is labeled with a fluorescent lectin whereas the other is not ( Fig. 1B; Beinhauer et al 1997;Alvarez-Tabarés et al 2007;Grallert et al 2007;Attanapola 2009;Martín-García and Mulvihill 2009). Alternatively, an additional fusion protein at a distinct location that emits at a different wavelength can be incorporated into the control strain (Fig.…”
Section: Mountingsupporting
confidence: 59%
“…Live-cell imaging confirmed that Myo52 made frequent long-distance cytoplasmic movements and concentrated to non-motile foci at the growing cell tips (Fig. 1B) (Grallert et al, 2007). By contrast, Myo52-1 failed to concentrate to the actin-patch-rich cell tips to the same extent as the wild-type protein and made relatively short and less frequent excursions within the cell (Fig.…”
Section: Motor Activity Of Myosin V Regulates Microtubule Catastrophementioning
confidence: 73%
“…Myo52 moves along Cdc8-actin polymers within the S. pombe cell and concentrates at actin-rich sites of cell growth (Grallert et al, 2007). Not only was the ability of Myo52 to localise to actin filaments or concentrate at regions of growth unaffected in the naa25 cells (Fig.…”
Section: Cellular Distribution and Dynamics Of Class I And V Myosin Amentioning
confidence: 93%